No learning rates needed: Introducing SALSA - Stable Armijo Line Search Adaptation - Kenneweg, Philip; Kenneweg, Tristan; Fumagalli, Fabian; Hammer, Barbara (2024 International Joint Conference on Neural Networks (IJCNN))
Keywords: Training; Schedules; Codes; Search methods; Source coding; Computer architecture; Transformers

Beyond TreeSHAP: Efficient Computation of Any-Order Shapley Interactions for Tree Ensembles - Muschalik, Maximilian; Fumagalli, Fabian; Hammer, Barbara; Huellermeier, Eyke (Proceedings of the AAAI Conference on Artificial Intelligence (AAAI))
While shallow decision trees may be interpretable, larger ensemble models like gradient-boosted trees, which often set the state of the art in machine learning problems involving tabular data, still remain black box models. As a remedy, the Shapley value (SV) is a well-known concept in explainable artificial intelligence (XAI) research for quantifying additive feature attributions of predictions. The model-specific TreeSHAP methodology solves the exponential complexity for retrieving exact SVs from tree-based models. Expanding beyond individual feature attribution, Shapley interactions reveal the impact of intricate feature interactions of any order. In this work, we present TreeSHAP-IQ, an efficient method to compute any-order additive Shapley interactions for predictions of tree-based models. TreeSHAP-IQ is supported by a mathematical framework that exploits polynomial arithmetic to compute the interaction scores in a single recursive traversal of the tree, akin to Linear TreeSHAP. We apply TreeSHAP-IQ on state-of-the-art tree ensembles and explore interactions on well-established benchmark datasets.
Keywords: Explainable Artificial Intelligence

SVARM-IQ: Efficient Approximation of Any-order Shapley Interactions through Stratification - Kolpaczki, Patrick; Muschalik, Maximilian; Fumagalli, Fabian; Hammer, Barbara; Huellermeier, Eyke (Proceedings of The 27th International Conference on Artificial Intelligence and Statistics (AISTATS))
Addressing the limitations of individual attribution scores via the Shapley value (SV), the field of explainable AI (XAI) has recently explored intricate interactions of features or data points. In particular, extensions of the SV, such as the Shapley Interaction Index (SII), have been proposed as a measure to still benefit from the axiomatic basis of the SV. However, similar to the SV, their exact computation remains computationally prohibitive. Hence, we propose with SVARM-IQ a sampling-based approach to efficiently approximate Shapley-based interaction indices of any order. SVARM-IQ can be applied to a broad class of interaction indices, including the SII, by leveraging a novel stratified representation. We provide non-asymptotic theoretical guarantees on its approximation quality and empirically demonstrate that SVARM-IQ achieves state-of-the-art estimation results in practical XAI scenarios on different model classes and application domains.

KernelSHAP-IQ: Weighted Least Square Optimization for Shapley Interactions - Fumagalli, Fabian; Muschalik, Maximilian; Kolpaczki, Patrick; Hüllermeier, Eyke; Hammer, Barbara (Proceedings of the 41st International Conference on Machine Learning (ICML))
The Shapley value (SV) is a prevalent approach of allocating credit to machine learning (ML) entities to understand black box ML models. Enriching such interpretations with higher-order interactions is inevitable for complex systems, where the Shapley Interaction Index (SII) is a direct axiomatic extension of the SV. While it is well-known that the SV yields an optimal approximation of any game via a weighted least square (WLS) objective, an extension of this result to SII has been a long-standing open problem, which even led to the proposal of an alternative index. In this work, we characterize higher-order SII as a solution to a WLS problem, which constructs an optimal approximation via SII and k-Shapley values (k-SII). We prove this representation for the SV and pairwise SII and give empirically validated conjectures for higher orders. As a result, we propose KernelSHAP-IQ, a direct extension of KernelSHAP for SII, and demonstrate state-of-the-art performance for feature interactions.

shapiq: Shapley interactions for machine learning - Muschalik, Maximilian; Baniecki, Hubert; Fumagalli, Fabian; Kolpaczki, Patrick; Hammer, Barbara; Huellermeier, Eyke (Advances in Neural Information Processing Systems (NeurIPS))

Approximating the shapley value without marginal contributions - Kolpaczki, Patrick; Bengs, Viktor; Muschalik, Maximilian; Hüllermeier, Eyke (Proceedings of the AAAI conference on Artificial Intelligence (AAAI))

Quote to explain: Using multimodal metalinguistic markers to explain large language models’ understanding capabilities - Belosevic, Milena; Buschmeier, Hendrik (ICMI Companion ’24: Companion Proceedings of the 26th International Conference on Multimodal Interaction)
Starting from the assumption that LLMs are systems bearing only formal but not functional linguistic competence, this short paper explores how the understanding capabilities of LLMs could be implicitly explained based on a “pause and refect” strategy. Specifically, we propose to include a virtual embodied agent in human interactions with LLM-based chatbots. The agent will use air quotes as multimodal metalinguistic markers to explicitly point to those parts of the LLM’s output that are relevant to explaining the LLM’s meaning understanding capabilities. At the same time, by scafolding users to perceive the output as ‘mentioned language’ inferred from a metalinguistic function of multimodal markers, the agent implicitly explains how the meaning of the output should be understood. In this proposal, users will actively participate in the co-construction of the implicit explanation by providing feedback and deciding when and to what extent the agent’s scafold (e.g., the air quotes) is used.

Revisiting the phenomenon of syntactic complexity convergence on German dialogue data - Wang, Yu; Buschmeier, Hendrik (Proceedings of the 20th Conference on Natural Language Processing (KONVENS 2024))
We revisit the phenomenon of syntactic complexity convergence in conversational interaction, originally found for English dialogue, which has theoretical implication for dialogical concepts such as mutual understanding. We use a modified metric to quantify syntactic complexity based on dependency parsing. The results show that syntactic complexity convergence can be statistically confirmed in one of three selected German datasets that were analysed. Given that the dataset which shows such convergence is much larger than the other two selected datasets, the empirical results indicate a certain degree of linguistic generality of syntactic complexity convergence in conversational interaction. We also found a different type of syntactic complexity convergence in one of the datasets while further investigation is still necessary.

How much does nonverbal communication conform to entropy rate constancy?: A case study on listener gaze in interaction - Wang, Yu; Xu, Yang; Skantze, Gabriel; Buschmeier, Hendrik (Findings of the Association for Computational Linguistics ACL 2024)
According to the Entropy Rate Constancy (ERC) principle, the information density of a text is approximately constant over its length. Whether this principle also applies to nonverbal communication signals is still under investigation. We perform empirical analyses of video-recorded dialogue data and investigate whether listener gaze, as an important nonverbal communication signal, adheres to the ERC principle. Results show (1) that the ERC principle holds for listener gaze; and (2) that the two linguistic factors syntactic complexity and turn transition potential are weakly correlated with local entropy of listener gaze.

Automatic reconstruction of dialogue participants’ coordinating gaze behavior from multiple camera perspectives - Riechmann, Alina Naomi; Buschmeier, Hendrik (Book of Abstracts of the 2nd International Multimodal Communication Symposium)

Disentangling Dialect from Social Bias via Multitask Learning to Improve Fairness - Spliethöver, Maximilian; Menon, Sai Nikhil; Wachsmuth, Henning (Findings of the Association for Computational Linguistics: ACL 2024)
Dialects introduce syntactic and lexical variations in language that occur in regional or social groups. Most NLP methods are not sensitive to such variations. This may lead to unfair behavior of the methods, conveying negative bias towards dialect speakers. While previous work has studied dialect-related fairness for aspects like hate speech, other aspects of biased language, such as lewdness, remain fully unexplored. To fill this gap, we investigate performance disparities between dialects in the detection of five aspects of biased language and how to mitigate them. To alleviate bias, we present a multitask learning approach that models dialect language as an auxiliary task to incorporate syntactic and lexical variations. In our experiments with African-American English dialect, we provide empirical evidence that complementing common learning approaches with dialect modeling improves their fairness. Furthermore, the results suggest that multitask learning achieves state-of-the-art performance and helps to detect properties of biased language more reliably.

Time-bin entanglement in the deterministic generation of linear photonic cluster states - Bauch, David; Köcher, Nikolas; Heinisch, Nils; Schumacher, Stefan (APL Quantum)
We theoretically investigate strategies for the deterministic creation of trains of time-bin entangled photons using an individual quantum emitter described by a Λ-type electronic system. We explicitly demonstrate the theoretical generation of linear cluster states with substantial numbers of entangled photonic qubits in full microscopic numerical simulations. The underlying scheme is based on the manipulation of ground state coherences through precise optical driving. One important finding is that the most easily accessible quality metrics, the achievable rotation fidelities, fall short in assessing the actual quantum correlations of the emitted photons in the face of losses. To address this, we explicitly calculate stabilizer generator expectation values as a superior gauge for the quantum properties of the generated many-photon state. With widespread applicability in other emitter and excitation–emission schemes also, our work lays the conceptual foundations for an in-depth practical analysis of time-bin entanglement based on full numerical simulations with predictive capabilities for realistic systems and setups, including losses and imperfections. The specific results shown in the present work illustrate that with controlled minimization of losses and realistic system parameters for quantum-dot type systems, useful linear cluster states of significant lengths can be generated in the calculations, discussing the possibility of scalability for quantum information processing endeavors.

Organic Room-Temperature Polariton Condensate in a Higher-Order Topological Lattice - Bennenhei, Christoph; Shan, Hangyong; Struve, Marti; Kunte, Nils; Eilenberger, Falk; Ohmer, Jürgen; Fischer, Utz; Schumacher, Stefan; Ma, Xuekai; Schneider, Christian; Esmann, Martin (ACS Photonics)

Swing-up dynamics in quantum emitter cavity systems: Near ideal single photons and entangled photon pairs - Heinisch, Nils; Köcher, Nikolas; Bauch, David; Schumacher, Stefan (Physical Review Research)
In the SUPER scheme (Swing-UP of the quantum EmitteR population), excitation of a quantum emitter is achieved with two off-resonant, red-detuned laser pulses. This allows the generation of high-quality single photons without the need of complex laser stray light suppression or careful spectral filtering. In the present work, we extend this promising method to quantum emitters, specifically semiconductor quantum dots, inside a resonant optical cavity. A significant advantage of the SUPER scheme is identified in that it eliminates re-excitation of the quantum emitter by suppressing photon emission during the excitation cycle. This, in turn, leads to almost ideal single-photon purity, overcoming a major factor typically limiting the quality of photons generated with quantum emitters in high-quality cavities. We further find that for cavity-mediated biexciton emission of degenerate photon pairs, the SUPER scheme leads to near-perfect biexciton initialization with very high values of polarization entanglement of emitted photon pairs. Published by the American Physical Society 2024

Topological edge and corner states in coupled wave lattices in nonlinear polariton condensates - Schneider, Tobias; Gao, Wenlong; Zentgraf, Thomas; Schumacher, Stefan; Ma, Xuekai (Nanophotonics)
Abstract Topological states have been widely investigated in different types of systems and lattices. In the present work, we report on topological edge states in double-wave (DW) chains, which can be described by a generalized Aubry-André-Harper (AAH) model. For the specific system of a driven-dissipative exciton polariton system we show that in such potential chains, different types of edge states can form. For resonant optical excitation, we further find that the optical nonlinearity leads to a multistability of different edge states. This includes topologically protected edge states evolved directly from individual linear eigenstates as well as additional edge states that originate from nonlinearity-induced localization of bulk states. Extending the system into two dimensions (2D) by stacking horizontal DW chains in the vertical direction, we also create 2D multi-wave lattices. In such 2D lattices multiple Su–Schrieffer–Heeger (SSH) chains appear along the vertical direction. The combination of DW chains in the horizonal and SSH chains in the vertical direction then results in the formation of higher-order topological insulator corner states. Multistable corner states emerge in the nonlinear regime.

Manipulating spectral topology and exceptional points by nonlinearity in non-Hermitian polariton systems - Wingenbach, Jan; Schumacher, Stefan; Ma, Xuekai (Physical Review Research)
Exceptional points (EPs), with their intriguing spectral topology, have attracted considerable attention in a broad range of physical systems, with potential sensing applications driving much of the present research in this field. Here, we investigate spectral topology and EPs in systems with significant nonlinearity, exemplified by a nonequilibrium exciton-polariton condensate. With the possibility to control loss and gain and nonlinearity by optical means, this system allows for a comprehensive analysis of the interplay of nonlinearities (Kerr type and saturable gain) and non-Hermiticity. Not only do we find that EPs can be intentionally shifted in parameter space by the saturable gain, but we also observe intriguing rotations and intersections of Riemann surfaces and find nonlinearity-enhanced sensing capabilities. With this, our results illustrate the potential of tailoring spectral topology and related phenomena in non-Hermitian systems by nonlinearity. Published by the American Physical Society 2024

Novel Phosphazenium Tetrafluoroborate Dopant Enables Efficient and Thermally Stable n‐Doped Organic Semiconductors - Wei, Huan; Guo, Jing; Liu, Heng; Wu, Tong; Chen, Ping‐An; Dong, Chuanding; Wang, Shu‐Jen; Schumacher, Stefan; Bai, Yugang; Lei, Ting; Wang, Suhao; Hu, Yuanyuan (Advanced Electronic Materials)
Abstract Thermal stability is crucial for doped organic semiconductors (OSCs) and their applications in organic thermoelectric (OTE) devices. However, the capacity of n‐dopants to produce thermally stable n‐doped OSC films has not been thoroughly explored, with few reports of high thermal stability. Here, a novel n‐dopant, phosphazenium tetrafluoroborate (P 2 BF 4 ) is introduced, which effectively induces n‐doping in N2200, P(PzDPP‐CT2) and several other commonly used OSCs. Remarkably, the electrical conductivity of P 2 BF 4 ‐doped OSC films remains almost unchanged even after heating at temperatures > 150 °C for 24 h, far superior to the films doped with benchmark N‐DMBI. The exceptional thermal stability observed in P 2 BF 4 ‐doped P(PzDPP‐CT2) films allows for stable operation of the corresponding organic thermoelectric devices at 150 °C for 16 h, a milestone not previously achieved. This study offers valuable insights into the development of n‐dopants capable of producing OSCs with outstanding thermal stability, paving the way for the practical realization of OTE devices with enhanced operation stability.

Dynamics of Electron–Hole Coulomb Attractive Energy and Dipole Moment of Hot Excitons in Donor–Acceptor Polymers - Bauch, Fabian; Dong, Chuan-Ding; Schumacher, Stefan (The Journal of Physical Chemistry C)

Charge transfer in superbase n-type doping of PCBM induced by deprotonation - Dong, Chuan-Ding; Bauch, Fabian; Hu, Yuanyuan; Schumacher, Stefan (Physical Chemistry Chemical Physics)
Charge transfer mechanism in the deprotonation-induced n-type doping of PCBM.

Photochemical Reaction Enabling the Engineering of Photonic Spin–Orbit Coupling in Organic-Crystal Optical Microcavities - Liang, Qian; Ma, Xuekai; Gu, Chunling; Ren, Jiahuan; An, Cunbin; Fu, Hongbing; Schumacher, Stefan; Liao, Qing (Journal of the American Chemical Society)